EDUKASI KESEHATAN GIGI DAN MULUT MELALUI PENGGUNAAN MEDIA ANIMASI PADA SISWA SD ISLAM NABILAH BATAM - Putri, Angga; Sarmini; Sri Nuraeni; Septia Asri; Rani Safitri Manullang (Jurnal Pendekar Nusantara, 2024)
The significance of providing oral health education to elementary school students is in its direct correlation to the overall health condition of the students. Physically and mentally fit students are a highly advantageous resource for the nation. Animation media possesses a significant impact on students' knowledge, making it highly ideal as an educational medium. The objective of this service is to enhance the students' understanding of oral hygiene at Nabilah Islamic Elementary School in Batam city, with a total of 64 pupils in the second grade. The utilization of animated media in education has been observed to significantly enhance students' knowledge. Evidently, the average pre-education knowledge is at 59, while the average post-education knowledge rises to 91.2. It is expected that schools and other educational advocates would cultivate this animation medium and explore further educational media that might enhance students' knowledge.